2004
DOI: 10.1097/01.prs.0000132856.69391.43
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable PLLA-PGA Plate and Screw Fixation in Pediatric Craniofacial Surgery: Clinical Experience in 1883 Patients

Abstract: The need to provide rigid bony fixation in the surgical treatment of craniofacial deformities has inspired an on-going evolution of surgical innovations and implants. Because of the young age of many treated craniosynostosis patients and the unique pattern of cranial vault growth, the extensive implantation of metal devices is potentially problematic. The use of resorbable plate and screw devices offers all of the benefits of rigid fixation without many of their potential risks. Since the introduction of resor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
167
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(176 citation statements)
references
References 19 publications
2
167
0
7
Order By: Relevance
“…screws or plates [1, [4][5][6] in oral and maxillofacial surgery [7]. Poly(lactide-co-glycolide) (PLGA) is one of the most often used biodegradable synthetic polymers [8].…”
Section: Introductionmentioning
confidence: 99%
“…screws or plates [1, [4][5][6] in oral and maxillofacial surgery [7]. Poly(lactide-co-glycolide) (PLGA) is one of the most often used biodegradable synthetic polymers [8].…”
Section: Introductionmentioning
confidence: 99%
“…The volume increase leads to an inherent increase in surface area, and because the soft tissue envelope remains unaltered, incision closure during this procedure can be challenging due to the high degree of tension, sometimes leading to the aforementioned wound healing difficulties. In fact, the degree of tension can be so high that some have been concerned about compression forces on the newly constructed calvarial vault postoperatively (11). We propose that intraoperative tissue expansion in the subgaleal plane is a means to reduce the tension on the closure and thereby reduce the risk of postoperative wound healing complications.…”
Section: Discussionmentioning
confidence: 99%
“…3 In a review of the use of resorbable plates and screws in 1883 craniofacial surgical cases, Eppley et al reported device failure from breakage of the plates that required reoperation in the postoperative period (0.3%) and delayed foreign body reactions (0.7%) that resulted in swelling and/or cyst formation. 6 Higher complication rates due to resorbable plates and screws were reported by Pearson et al (17%) 22 and Sanger et al (15.3%), including palpable plates and an instance in which the absorbable plates were surgically removed due to erythema. 26 Furthermore, there are the inherent challenges in nearly all surgeries and operative techniques: blood loss, extended surgical times, narrow application, or lack of an aesthetically acceptable result.…”
mentioning
confidence: 87%